What Universities Owe Democracy - Daniels, Ronald J. (Ronald Joel), 1959-; Shreve, Grant, 1984-; Spector, Phillip, 1976- (Book collections on Project MUSE., 2021)
"This book identifies four distinct functions of American higher education that colleges and universities have acquired over the past two hundred years and that are integral to liberal democracy: social mobility, citizenship education, the discovery and communication of knowledge, and the cultivation of a pluralistic society. Each chapter takes up one of these functions to analyze and assess"--